1971
DOI: 10.1029/jb076i005p01197
|View full text |Cite
|
Sign up to set email alerts
|

Structure and isostasy of the Baikal Rift and the mechanism of rifting

Abstract: The Baikal rift is the most important of a system of rift valleys located in the USSR. A comparison of geological and geophysical data for the Baikal rift and other rift zones of the earth leads to the conclusion that their origin is determined by similar deep‐seated processes. Some mechanisms of rifting suggested earlier are considered. It is shown that rift‐valley formation cannot result from collapse of the central parts of large crustal arches. The concept of Vening‐Meinesz that considers rifting to result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(45 citation statements)
references
References 4 publications
2
40
0
3
Order By: Relevance
“…Flow within the ductile layer during rifting is considered to accommodate the balance of crustal thinning. The observations in Biscay best support a model of rift valley formation by subsidence of a crustal wedge due to normal faulting under tension of the brittle upper layer with compensatory flow or thinning taking place in a lower ductile layer (Bolt, 1971;Artemjev and Artyushkov, 1971;Montadert et al, this volume). Heat flow data for the Biscay margin (Foucher et al, this volume) can only be interpreted in terms of thinning of the ductile lower part of the crust and not in terms of phase changes or intrusions.…”
Section: Rifting and Subsidencesupporting
confidence: 50%
“…Flow within the ductile layer during rifting is considered to accommodate the balance of crustal thinning. The observations in Biscay best support a model of rift valley formation by subsidence of a crustal wedge due to normal faulting under tension of the brittle upper layer with compensatory flow or thinning taking place in a lower ductile layer (Bolt, 1971;Artemjev and Artyushkov, 1971;Montadert et al, this volume). Heat flow data for the Biscay margin (Foucher et al, this volume) can only be interpreted in terms of thinning of the ductile lower part of the crust and not in terms of phase changes or intrusions.…”
Section: Rifting and Subsidencesupporting
confidence: 50%
“…Extensional tectonics has attracted great interests from geoscientists for a long time. Since the original lithospheric stretching model of Artemjev and Artyushkov (1971) and the further modified models by McKenzie (1978), a huge amount of work has been done in the field and can be found in numerous papers (e.g., Wernicke and Burchfiel, 1982;England and McKenzie, 1982;Buck and Toksöz, 1983;England, 1983;Turcotte and Emerman, 1983;England and Houseman, 1985;Cloetingh and Wortel, 1986;Lister et al, 1986;England, 1986a, 1986b;Braun and Beaumont, 1987;Lister and Davis, 1989;Govers and Wortel, 1993;Huismans et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cobbold et al (1971) showed that if the theory of internal instability for folding, as developed by Biot (1957Biot ( , 1964a, is used for a compression direction orthogonal to the anisotropy orientation, then structures can form that are similar to pinch-and-swell structure (they also used the term internal boudins). Artemjev and Artyushkov (1971) were probably the first to suggest that rift systems are caused by crustal thinning due to a necking instability during lithospheric extension. It was subsequently shown that lithospheric necking for slow spreading rates (1-3 cm yr −1 ) is feasible for creep flow laws considered typical for the lithosphere (Tapponnier and Francheteau, 1978).…”
Section: Multilayer Neckingmentioning
confidence: 99%
“…7b), the Baikal rift (Artemjev and Artyushkov, 1971) or the western Mediterranean back-arc basin (Gueguen et al, 1997). Furthermore, most kinematic or semi-kinematic (including flexure) models of lithospheric thinning and associated sedimentary basin formation implicitly assume a continuous necking of the lithosphere (McKenzie, 1978;Kooi et al, 1992).…”
Section: Lithospheric Neckingmentioning
confidence: 99%